Evaluasi Dampak Kawasan Ekonomi Khusus (KEK) Mandalika Terhadap Pertumbuhan Ekonomi Daerah di Provinsi Nusa Tenggara Barat: Pendekatan Difference-In-Differences - Nisrina Yasyfi Mumtaz (Journal of Economics, Management, and Accounting, 2026)
The Mandalika Special Economic Zone (SEZ) was established as a place-based development policy to stimulate regional economic activity in West Nusa Tenggara (NTB), yet quantitative evidence on its growth impact remains limited. This study examines whether the activation of the Mandalika SEZ affected economic growth in Central Lombok relative to other districts/municipalities in NTB. The analysis applies a Difference-in-Differences (DiD) approach using annual panel data for 10 regions over 2014–2024, defining Central Lombok as the treated unit and the remaining regions as controls, while controlling for HDI, population, unemployment, and investment. The estimates show a positive Treat × Post coefficient, but the effect is not statistically significant in both the baseline and two-way fixed effects specifications. Overall, the findings suggest that within the observed period, the Mandalika SEZ has not yet produced a statistically robust growth differential in real GRDP per capita for the host region relative to comparison areas.